Retropharyngeal abscess, submandibular abscess, and regio colli abscess with bronchopneumonia in a 2.5-month-old boy - Irhamna Yusra; Finny Fitry Yani (Majalah Kedokteran Andalas, 2019)
Deep neck space infections (DNSIs) in pediatric require more intimate management because of their rapidly progressive nature. Delay in diagnosis and treatment may lead to life-threatening complications. Objective: To report DNSIs as one of emergency case in children. Early diagnosis and immediate management can decrease morbidity and mortality rate in children. Case: A case of a 2.5-month-old boy with chief complain breathlessness due to deep neck space infections and bronchopneumonia. Patient was getting better after surgical drainage. Conclusions: It most commonly occurs in children younger than four years of age having medical history of streptococcal pharyngitis, rarely as a complication of recent trauma, odontogenic infection or extension of vertebral osteomyelitis. Management often consists of antimicrobial therapy and surgical drainage. With the cooperation of ENT specialist and pediatrician/pediatric infectious disease specialist. Management in PICU is mandatory due to high risk of complications.